Quartz sand for fracturing and preparation method thereof

By combining the modified epoxy resin coating agent with quartz sand, the problem of insufficient flow diversion and crushing rate of existing fracturing quartz sand is solved, and quartz sand for fracturing with high mechanical strength and good flow diversion ability is achieved preparation.

CN119490842AActive Publication Date: 2025-02-21SICHUAN GUANGKUANG NEW MATERIALS CO LTD

Patent Information

Application Number
CN202411626794.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-21
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The crushing rate and flow diversion capacity of existing fracturing quartz sand is poor, and it is difficult to meet the needs of high mechanical strength and good flow diversion capacity.

Method used

By combining a modified epoxy resin coating agent with quartz sand, a fracturing quartz sand with high mechanical strength and good flow guide capability was prepared. Modified epoxy resin coating agent is prepared by reaction of PEG800, tolyl 2,6-diisocyanate, bisphenol A type epoxy resin and aminopropyl methyl polysiloxane, giving the resin high reactivity and resistance. Thermal and flexible Si-O bonds.

Benefits of technology

The mechanical strength and flow diversion capacity of quartz sand for fracturing are improved, the crushing rate is reduced, and the needs of high spherical, low volume density, low crushing rate and high flow diversion capacity are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005134948560000021
    Figure BDA0005134948560000021
  • Figure BDA0005134948560000031
    Figure BDA0005134948560000031
  • Figure BDA0005134948560000041
    Figure BDA0005134948560000041
Patent Text Reader

Abstract

The invention discloses quartz sand for fracturing and a preparation method thereof, and relates to the technical field of quartz sand for fracturing. The quartz sand for fracturing comprises the following raw materials in parts by weight: 50 parts of quartz sand and 5-8 parts of an organic silicon modified epoxy resin coating agent. The preparation method comprises the following steps: carrying out a reaction on PEG800 and 2, 6-toluene diisocyanate to prepare a transparent colloidal solid, carrying out a reaction on the transparent colloidal solid and bisphenol A epoxy resin to prepare an intermediate, and carrying out a reaction on the intermediate and aminopropyl methyl polysiloxane to prepare the organosilicon modified epoxy resin coating agent. The prepared quartz sand for fracturing has high sphericity, low density and high flow conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of quartz sand for fracturing, and in particular to quartz sand for fracturing and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of the world economy and the rapid progress of science and technology, the demand for oil and natural gas remains high. Hydraulic fracturing technology is an important means to increase the production of oil and gas wells. It has been widely used in the development of various oil and gas wells. In the process of hydraulic fracturing, the role of proppant is crucial. Proppant is a key material for fracturing construction of low permeability oil and gas wells and shale gas reservoirs. It is a product with high added value. Its performance determines the success or failure of hydraulic fracturing technology and also affects the service life of oil and gas wells. Quartz sand is a natural mineral with high hardness, good stability and wide distribution. It is mainly produced in river beaches, deserts or coastal areas. Quartz sand is abundant in resources, cheap, low in density, and easy to pump with fracturing fluid, but its compressive strength is low, and its conductivity is greatly reduced after crushing. Therefore, it is particularly important to develop a proppant with high sphericity, low bulk density, low crushing rate and high conductivity.

[0003] A Chinese invention patent with publication number CN112876118A discloses a quartz sand for fracturing and a preparation method thereof. The quartz sand for fracturing comprises a quartz sand aggregate and a coating layer coated on the surface of the quartz sand aggregate, and the coating layer is composed of the following raw materials: fly ash, coal gangue, clay, kaolin, silicon micropowder, silane coupling agent, and metal mineral powder. The quartz sand for fracturing prepared by the invention has a simple preparation method and strong corrosion resistance, but its crushing rate and conductivity are poor. Summary of the invention

[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide quartz sand for fracturing and a preparation method thereof.

[0005] To achieve the above object, the present invention is implemented through the following technical solutions:

[0006] A quartz sand for fracturing comprises the following raw materials in parts by weight: 25-50 parts of quartz sand and 5 parts of modified epoxy resin coating agent.

[0007] The modified epoxy resin coating agent is prepared by the following method:

[0008] S1: Under nitrogen protection, DMF and 2,6-diisocyanatotoluene were added to the reactor in sequence, stirred and dissolved, and the temperature was raised to 50-70°C. Then PEG800 was slowly added dropwise, and the catalyst dibutyltin dilaurate was added after the addition. The reaction was continued for 4-6 hours, and a transparent colloidal solid was obtained after post-treatment. The reaction equation is shown as follows:

[0009]

[0010] S2: Under nitrogen protection, acetone, transparent colloidal solid, and bisphenol A epoxy resin are added to the reactor in sequence, stirred and dissolved, heated to 80-100°C, and a catalyst dibutyltin dilaurate is added. After reacting for 6-8 hours, the intermediate is obtained by post-treatment. The reaction equation is as follows:

[0011]

[0012] S3: DMF, intermediate and aminopropylmethylpolysiloxane are added to the reactor in sequence, stirred and dissolved, heated to 80-120°C, reacted for 4-6h, cooled to 60-80°C, triethylamine was added for neutralization, and the organosilicon-modified epoxy resin coating agent was obtained by vacuum distillation. The reaction equation is as follows:

[0013]

[0014]

[0015] Among them, m, n, o, r, s, t, p, and q are natural numbers.

[0016] In the step S1, the mass ratio of DMF, 2,6-diisocyanatotoluene, PEG800, and dibutyltin dilaurate is 20:(8-10):(4-6):(0.01-0.03).

[0017] In the step S2, the mass ratio of acetone, transparent colloidal solid, bisphenol A epoxy resin and dibutyltin dilaurate is 50:(6-8):(10-12):(0.05-0.08).

[0018] In the step S3, the feed mass ratio of DMF, intermediate and aminopropylmethylpolysiloxane is 50:(8-12):(10-15).

[0019] The method for preparing quartz sand for fracturing comprises the following steps:

[0020] S1: Weigh quartz sand by weight, wash it 3 times with deionized water, wash it once with anhydrous ethanol, and wash it once with petroleum ether, and dry it in an electric heated blast drying oven at 80-100° C. for 4-6 hours to obtain a precursor;

[0021] S2: mixing the organosilicon-modified epoxy resin coating agent and DMF at room temperature to obtain a viscous modified epoxy resin coating agent;

[0022] S3: Add the precursor and the viscous modified epoxy resin coating agent into the reactor, stir at 100-120° C. for 4-6 hours, and then dry at 105-115° C. for 10-12 hours to obtain quartz sand for fracturing.

[0023] Due to the adoption of the above technical solution, the beneficial effects of the present invention include:

[0024] (1) The present invention prepares a transparent colloidal solid by reacting PEG800 and 2,6-toluene diisocyanate, then reacts the transparent colloidal solid with bisphenol A epoxy resin to prepare an intermediate, and then reacts with aminopropyl methyl polysiloxane to prepare an organosilicon-modified epoxy resin coating agent.

[0025] (2) The silicone-modified epoxy resin coating agent prepared by the present invention contains a large number of oxidizing functional groups, wherein the epoxy and hydroxyl groups in the epoxy resin give the resin high reactivity, making the resin have strong cohesion and adhesion, and the benzene ring gives the resin heat resistance and rigidity. On the other hand, by modifying the epoxy resin with silicone, the advantages of the two polymers are complemented, and flexible Si-O bonds are introduced inside the epoxy. The Si-O bonds can make the polymer chain segments rotate more easily, which can reduce the internal stress of the epoxy resin, thereby greatly improving the fracture toughness of the epoxy resin, so that the prepared quartz sand for fracturing has high mechanical strength and good flow conductivity. DETAILED DESCRIPTION

[0026] The invention will be further described below with reference to the embodiments, but the invention is not limited to these embodiments.

[0027] Example 1

[0028] Preparation of silicone modified epoxy resin coating agent:

[0029] S1: Under nitrogen protection, 200g DMF and 80g 2,6-diisocyanatotoluene ester were added to the reactor in sequence, stirred and dissolved, and the temperature was raised to 50°C. Then 40g PEG800 was slowly added dropwise for 20min. After the addition, 0.1g catalyst dibutyltin dilaurate was added. The reaction was continued for 6h. Then 500ml ice water was added for precipitation and filtration. The mixture was dried under vacuum at 40°C for 12h to obtain a transparent colloidal solid.

[0030] S2: Under nitrogen protection, 500 g of acetone, 60 g of transparent colloidal solid, and 100 g of bisphenol A epoxy resin (E51) were added to the reactor in sequence, stirred and dissolved, heated to 80°C, 0.5 g of catalyst dibutyltin dilaurate was added, reacted for 8 h, and distilled under reduced pressure at 50°C for 6 h to obtain the intermediate;

[0031] S3: Add 500g DMF, 80g intermediate and 100g aminopropyl methyl polysiloxane into the reactor in sequence, stir to dissolve, heat to 80°C, react for 6h, cool to 60°C, add 150ml triethylamine to neutralize, and distill at 60°C under reduced pressure for 6h to obtain the organosilicon-modified epoxy resin coating agent.

[0032] Example 2

[0033] Preparation of silicone modified epoxy resin coating agent:

[0034] S1: Under nitrogen protection, 200g DMF and 90g 2,6-diisocyanatotoluene ester were added to the reactor in sequence, stirred and dissolved, and the temperature was raised to 60°C. Then, 50g PEG800 was slowly added dropwise for 25min. After the addition, 0.2g of catalyst dibutyltin dilaurate was added. The reaction was continued for 5h. Then, 500ml ice water was added for precipitation and filtration. The mixture was dried under vacuum at 50°C for 10h to obtain a transparent colloidal solid.

[0035] S2: Under nitrogen protection, 500 g of acetone, 70 g of transparent colloidal solid, and 110 g of bisphenol A epoxy resin (E51) were added to the reactor in sequence, stirred and dissolved, heated to 90°C, 0.65 g of catalyst dibutyltin dilaurate was added, reacted for 7 h, and distilled at 60°C under reduced pressure for 5 h to obtain the intermediate;

[0036] S3: Add 500g DMF, 100g intermediate and 125g aminopropyl methyl polysiloxane into the reactor in sequence, stir to dissolve, heat to 100°C, react for 5h, cool to 70°C, add 180ml triethylamine to neutralize, and distill at 70°C under reduced pressure for 5h to obtain the silicone-modified epoxy resin coating agent.

[0037] Example 3

[0038] Preparation of silicone modified epoxy resin coating agent:

[0039] S1: Under nitrogen protection, 200g DMF and 100g 2,6-diisocyanatotoluene ester were added to the reactor in sequence, stirred to dissolve, heated to 70°C, and then 60g PEG800 was slowly added dropwise for 30min. After the addition, 0.3g catalyst dibutyltin dilaurate was added, reacted for 4h, and then 500ml ice water was added for precipitation and filtration, and vacuum dried at 60°C for 8h to obtain a transparent colloidal solid;

[0040] S2: Under nitrogen protection, 500 g of acetone, 80 g of transparent colloidal solid, and 120 g of bisphenol A epoxy resin (E51) were added to the reactor in sequence, stirred to dissolve, heated to 100°C, 0.8 g of catalyst dibutyltin dilaurate was added, reacted for 6 h, and distilled under reduced pressure at 70°C for 4 h to obtain the intermediate;

[0041] S3: Add 500g DMF, 120g intermediate and 150g aminopropyl methyl polysiloxane into the reactor in sequence, stir to dissolve, heat to 120°C, react for 4h, cool to 80°C, add 200ml triethylamine to neutralize, and distill at 80°C under reduced pressure for 4h to obtain the organosilicon-modified epoxy resin coating agent.

[0042] Example 4

[0043] Preparation of quartz sand for fracturing:

[0044] S1: Weigh 500 g of quartz sand, wash it with deionized water for 3 times (500 g of deionized water is used each time), wash it with 500 g of anhydrous ethanol once, and then wash it with 300 g of petroleum ether once, and dry it in an electric blast drying oven at 80° C. for 6 h to obtain a precursor;

[0045] S2: 50 g of the organosilicon-modified epoxy resin coating agent (prepared in Example 1) and 100 g of DMF were mixed at room temperature to obtain a viscous organosilicon-modified epoxy resin coating agent;

[0046] S3: 500 g of the precursor and 150 g of a viscous silicone-modified epoxy resin coating agent were added into a reactor, stirred at 100° C. for 6 h, and then dried at 105° C. for 12 h to obtain quartz sand for fracturing.

[0047] Example 5

[0048] Preparation of quartz sand for fracturing:

[0049] S1: Weigh 500 g of quartz sand, wash it 3 times with deionized water (500 g of deionized water each time), wash it once with 500 g of anhydrous ethanol, and then wash it once with 300 g of petroleum ether, and dry it in an electric blast drying oven at 90° C. for 5 h to obtain a precursor;

[0050] S2: 65 g of the organosilicon-modified epoxy resin coating agent (prepared in Example 2) and 130 g of DMF were mixed at room temperature to obtain a viscous organosilicon-modified epoxy resin coating agent;

[0051] S3: 500 g of the precursor and 195 g of a viscous silicone-modified epoxy resin coating agent were added into a reactor, stirred at 110° C. for 5 h, and then dried at 110° C. for 11 h to obtain quartz sand for fracturing.

[0052] Example 6

[0053] Preparation of quartz sand for fracturing:

[0054] S1: Weigh 500 g of quartz sand, wash it with deionized water for 3 times (500 g of deionized water is used each time), wash it with 500 g of anhydrous ethanol once, and then wash it with 300 g of petroleum ether once, and dry it in an electric blast drying oven at 100 ° C for 4 h to obtain a precursor;

[0055] S2: 80 g of the organosilicon-modified epoxy resin coating agent (prepared in Example 3) and 160 g of DMF were mixed at room temperature to obtain a viscous organosilicon-modified epoxy resin coating agent;

[0056] S3: 500 g of the precursor and 240 g of a viscous silicone-modified epoxy resin coating agent were added into a reactor, stirred at 120° C. for 4 h, and then dried at 115° C. for 10 h to obtain quartz sand for fracturing.

[0057] Comparative Example 1

[0058] The preparation method of quartz sand for fracturing is as follows: weigh 500g of quartz sand, wash it with deionized water for 3 times (500g of deionized water is used each time), wash it with 500g of anhydrous ethanol once, and then wash it with 300g of petroleum ether once, and dry it in an electric blast drying oven at 90°C for 5h to obtain quartz sand for fracturing.

[0059] Comparative Example 2

[0060] The preparation method of quartz sand for fracturing is basically the same as that of Example 5, except that the organosilicon-modified epoxy resin coating agent (prepared in Example 2) is replaced by an equal weight of the intermediate prepared in step S2 of Example 2.

[0061] Comparative Example 3

[0062] The preparation method of quartz sand for fracturing is basically the same as that of Example 5, except that the organosilicon-modified epoxy resin coating agent (prepared in Example 2) is replaced by an equal weight of aminopropylmethylpolysiloxane.

[0063] Comparative Example 4

[0064] The preparation method of quartz sand for fracturing is:

[0065] S1: Weigh 500 g of quartz sand, wash it 3 times with deionized water (500 g of deionized water each time), wash it once with 500 g of anhydrous ethanol, and then wash it once with 300 g of petroleum ether, and dry it in an electric blast drying oven at 90° C. for 5 h to obtain a precursor;

[0066] S2: 29 g of the intermediate (prepared in step S2 of Example 2), 36 g of aminopropylmethylpolysiloxane and 130 g of DMF were mixed at room temperature to obtain a coating agent;

[0067] S3: 500 g of the precursor and 195 g of the coating agent were added into the reactor, stirred at 110° C. for 5 h, and then dried at 110° C. for 11 h to obtain quartz sand for fracturing.

[0068] Comparative Example 5

[0069] The preparation method of quartz sand for fracturing is:

[0070] S1: Weigh 500 g of quartz sand, wash it 3 times with deionized water (500 g of deionized water each time), wash it once with 500 g of anhydrous ethanol, and then wash it once with 300 g of petroleum ether, and dry it in an electric blast drying oven at 90° C. for 5 h to obtain a precursor;

[0071] S2: 15 g of a transparent colloidal solid (prepared in step S1 of Example 2), 23 g of a bisphenol A epoxy resin (E51), 27 g of aminopropylmethylpolysiloxane and 130 g of DMF were mixed at room temperature to obtain a coating agent;

[0072] S3: 500 g of the precursor and 195 g of the coating agent were added into the reactor, stirred at 110° C. for 5 h, and then dried at 110° C. for 11 h to obtain quartz sand for fracturing.

[0073] Comparative Example 6

[0074] The method for preparing quartz sand for fracturing is basically the same as that in Example 5, except that the organosilicon-modified epoxy resin coating agent (prepared in Example 2) in step S2 is replaced by an equal weight of the membrane material prepared in step (1) of Example 3 in Publication No. CN117625171A.

[0075] Comparative Example 7

[0076] A quartz sand for fracturing is produced by using the raw material composition and process in Example 2 of the Chinese invention patent specification with publication number CN112876118A.

[0077] The epoxy resin used in the examples and comparative examples of the present application is of model E51, purchased from Hunan Baling Petrochemical Company; the quartz sand specification is 140 mesh, purchased from Inner Mongolia Changfan Quartz Sand Co., Ltd.; aminopropyl methyl polysiloxane was purchased from American Gailest 6-7Psil, where p=6-7, q=93-94.

[0078] The quartz sand for fracturing prepared in Examples 4-6 of the present application and Comparative Examples 1-7 was tested for sphericity, bulk density, crushing rate and conductivity. The test results are shown in Table 1.

[0079] The sphericity, bulk density and crushing rate of quartz sand for fracturing are measured and calculated in accordance with SY / T5108-2014 "Test Method for Performance of Proppants for Hydraulic Fracturing and Gravel Packing Operations", and the conductivity is measured and calculated in accordance with SY / T6302-2019 "Test Method for Conductivity of Fracturing Proppants".

[0080] Table 1

[0081]

[0082]

[0083] It can be seen from Table 1 that the quartz sand for fracturing prepared in Examples 4-6 of the present application has excellent sphericity, bulk density, crushing rate and conductivity.

[0084] Comparative Example 1 is a comparative example prepared without adding an organosilicon-modified epoxy resin coating agent. From the data in Table 1, it can be seen that the crushing rate is 4.96% at 69 MPa and the flow conductivity is 27.21 μm. 2 ·cm.

[0085] The organic silicon modified epoxy resin coating agent added in Comparative Example 2 is the intermediate prepared in step S2 of Example 2. As can be seen from Table 1, its crushing rate is 4.58% at 69 MPa and its flow conductivity is 30.45 μm. 2 ·cm.

[0086] The silicone-modified epoxy resin coating agent added in Comparative Example 3 is aminopropylmethylpolysiloxane. As can be seen from Table 1, its breakage rate is 4.21% at 69 MPa and its flow conductivity is 31.68 μm. 2 ·cm.

[0087] The organic silicon modified epoxy resin coating agent added in Comparative Example 4 is 29g of the intermediate prepared in step S2 of Example 2 and 36g of aminopropylmethylpolysiloxane. It can be seen from Table 1 that the crushing rate is 3.45% at 69MPa and the flow conductivity is 35.23μm 2 ·cm.

[0088] The silicone-modified epoxy resin coating agent added in Comparative Example 5 is 15 g of a transparent colloidal solid (prepared in step S1 of Example 2), 23 g of bisphenol A epoxy resin (E51) and 27 g of aminopropylmethylpolysiloxane. As can be seen from Table 1, the crushing rate is 3.56% at 69 MPa and the flow conductivity is 34.84 μm. 2 ·cm.

[0089] Comparative Example 6 is a amphiphobic modified quartz sand proppant made by the raw material composition and process in Table 2 of the Chinese invention patent specification of CN115851254A. As can be seen from Table 1, its crushing rate is 3.89% at 69MPa and its conductivity is 34.32μm. 2 ·cm.

[0090] Comparative Example 7 is a quartz sand for fracturing made by using the raw material composition and process in Example 2 of the Chinese invention patent specification with publication number CN112876118A. As can be seen from Table 1, its crushing rate is 10.32% at 69MPa and its conductivity is 15.25μm. 2 ·cm.

[0091] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. However, any equivalent changes, modifications and evolutions made by ordinary technicians in the field without departing from the scope of the technical solution of the present invention by using the technical content disclosed above are all equivalent embodiments of the present invention. At the same time, any equivalent changes, modifications and evolutions made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the technical solution of the present invention.

Claims

1. A quartz sand for fracturing, characterized in that: The quartz sand for fracturing comprises the following raw materials in parts by weight: 50 parts of quartz sand and 5-8 parts of organosilicon-modified epoxy resin coating agent; The organosilicon-modified epoxy resin coating agent is prepared by the following method: S1: Under nitrogen protection, DMF and 2,6-diisocyanatotoluene were added to the reactor in sequence, stirred and dissolved, and the temperature was raised to 50-70°C, and then PEG800 was slowly added dropwise. After the addition, the catalyst dibutyltin dilaurate was added, and the reaction was carried out for 4-6 hours. After post-treatment, a transparent colloidal solid was obtained; S2: Under nitrogen protection, acetone, transparent colloidal solid, and bisphenol A epoxy resin are added to the reactor in sequence, stirred and dissolved, heated to 80-100°C, and a catalyst dibutyltin dilaurate is added, reacted for 6-8h, and post-treated to obtain an intermediate; S3: Add DMF, intermediate and aminopropylmethylpolysiloxane into the reactor in sequence, stir and dissolve, heat to 80-120°C, react for 4-6h, cool to 60-80°C, add triethylamine for neutralization, and distill under reduced pressure to obtain the organosilicon-modified epoxy resin coating agent.

2. The quartz sand for fracturing according to claim 1, characterized in that: In the step S1, the mass ratio of DMF, 2,6-diisocyanatotoluene, PEG800, and dibutyltin dilaurate is 20:(8-10):(4-6):(0.01-0.03).

3. The quartz sand for fracturing according to claim 1, characterized in that: In the step S2, the mass ratio of acetone, transparent colloidal solid, bisphenol A epoxy resin and dibutyltin dilaurate is 50:(6-8):(10-12):(0.05-0.08).

4. The quartz sand for fracturing according to claim 1, characterized in that: In the step S3, the feed mass ratio of DMF, intermediate and aminopropylmethylpolysiloxane is 50:(8-12):(10-15).

5. A method for preparing quartz sand for fracturing according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1: Weigh quartz sand by weight, wash it 3 times with deionized water, wash it once with anhydrous ethanol, and wash it once with petroleum ether, and dry it in an electric heated blast drying oven at 80-100° C. for 4-6 hours to obtain a precursor; S2: mixing the organosilicon-modified epoxy resin coating agent and DMF at room temperature to obtain a viscous modified epoxy resin coating agent; S3: Add the precursor and the viscous modified epoxy resin coating agent into the reactor, stir at 100-120° C. for 4-6 hours, and then dry at 105-115° C. for 10-12 hours to obtain quartz sand for fracturing.

Citation Information

Patent Citations

  • Quartz sand for fracturing and preparation method thereof

    CN112876118A

  • Amphiphobic and oleophobic modified quartz sand proppant and preparation method thereof

    CN115851254A

  • Flash coating treatments for proppant solids

    CN105793386A

  • Pressure activated curable resin coated proppants with high oil permeability

    CN108368423A

  • Polyurethane based propping agent coatings

    CN110557951A

Cited By

  • Oil-permeable and water-blocking coated quartz sand for fracturing and preparation method of oil-permeable and water-blocking coated quartz sand

    CN121064827A